Does analyst ESG experience matter? - Kopita, Anastasia; Petrou, Zacharias (My University, 2025)
We examine the relationship between analysts' task-specific experience in the context of ESG information and the informativeness of their stock recommendation revisions. While sell-side analysts incorporate ESG information in their valuation process and research reports, previous studies have indicated that the increased availability of ESG information in the market poses challenges for analysts to issue incrementally informative reports. Building upon existing literature that highlights systematic differences in analysts' performance that is attributed to their experience, we introduce a measure of financial analysts' ESG experience. We document a positive association between our proxy of analyst ESG experience and market reactions to their recommendation revisions. Our findings also show that analysts' ESG experience contributes to the interpretation of information included in firm ESG reports. We further find support for a stronger association between the market reaction and our ESG-experience proxy when firms exhibit lower levels of ESG disclosure and when they face higher external scrutiny due to their exposure to ESG-related risks. Our results are robust when considering analysts' innate and forecasting ability and when additional specifications are applied.